(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Friendship plays a significant role in human life and has a strong influence on personal development, emotional well-being, and social interaction. True friendship is based on trust, respect, understanding, and mutual support. Friends help individuals overcome difficulties, share happiness, and feel less lonely. This article discusses the importance of friendship in our life, its psychological and social benefits, and its role in shaping a positive personality. The paper also highlights how friendship contributes to mental health and strengthens social bonds in society.